Soil Fertility Management for Wildlife Food Plots - Cheryl L. Mackowiak (EDIS)
SL-248, 4-page illustrated fact sheet by C.L Mackowiak, includes sections on soil sampling, soil analyses, soil pH/liming, fertilizer recommendations, and organic fertilizers. Published by the UF Department of Soil and Water Science, March 2007.